Treatment update for autoimmune/immune-mediated central nervous system diseases - Wu, Jiayi; Li, Xuewei; Peng, Jun; Fu, Wan; Chen, Shuangxi; Wu, Heng (Folia Neuropathologica, 2025)
Autoimmune/immune-mediated central nervous system (CNS) diseases are chronic, inflammatory, autoimmune diseases, such as multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and autoimmune encephalitis (AE). A common pathological feature of these diseases is the targeting of the host’s immune system against autoantigens expressed by the CNS. In recent years, immunomodulatory therapeutic drugs and methods with different targets have emerged. Therefore, obtaining a more comprehensive and in-depth understanding of the characteristics, adverse reactions and indications of existing therapeutic drugs is essential to develop individualized therapies based on each patient’s characteristics, delay the progression of disorders and enhance the life quality of these patients. Although MS, NMOSD, and AE are all associated with immune inflammation, there are considerable differences in clinical treatment. Certain drugs may be approved for only one of these diseases, while other drugs may be suitable for all three. This review systematically describes the characteristics and scope of application of various drugs, including potential drugs under development, as well as non-drug therapeutic approaches.